Weed Control With Saflufenacil Singly and Mixture in Immature Oil Palm on Peat Land - Muhammad Iqbal; Edison Purba; Lisa Mawarni (Universitas Sumatera Utara, 2018)
The of a weed of immature oil palm on peat area is generally dominated by ferns as Stenochlaena palustris and Biserrata nephrolepis. Herbicide used to control ferns on peat is such limited. This research aimed to evaluate the bioefficacy of saflufenacil alone and combination with other herbicide ( glifosat, glufosinat, paraquat, metsulfuron methyl ) on peat land. This research is used randomized complete block design non factorial with there were 10 different herbicide treatment including paraquat (1500 g a.i.ha-1), glufosinat (3500 g a.i.ha-1), glifosat ( 1500 g a.i.ha-1), saflufenacil (75 g a.i.ha-1), saflufenacil (60 g a.i.ha-1) + paraquat (1500 g a.i.ha-1), saflufenacil (75 g a.i.ha-1) + glifosat (1500 g a.i.ha-1), saflufenacil (75 g a.i.ha-1) + glufosinat (1500 g a.i.ha-1), saflufenacil (75 g a.i.ha-1) + metil metsufuron (75 g a.i.ha-1), saflufenacil (75 g a.i.ha-1) + ( paraquat 1500 g a.i.ha-1) and without control. The highest percentage (88,1%) of weed control visually is caused by saflufenacil 75 g a.i.ha-1 + paraquat 1500 g a.i.ha-1 whereas the lowest (50,1%) is due to saflufenacil 75 g a.i.ha-1. Similarly the highest mortality of Stenochlaena palustris (86,94%) is caused by saflufenacil 75 g a.i.ha-1 + paraquat 1500 g a.i.ha-1. The highest mortality of Nephrolepis biserrata (74,07%) is due to saflufenacil 75 g a.i.ha-1 + metil metsulfuron 75 g a.i.ha-1. Keywords : oil palm, peat land, saflufenacil, weed control.